Whole-Genome Sequencing Reveals Exonic Variation of ASIC5 Gene Results in Recurrent Pregnancy Loss - Al Qahtani, Nourah H.; AbdulAzeez, Sayed; Almandil, Noor B.; Fahad Alhur, Norah; Alsuwat, Hind Saleh; Al Taifi, Hatoon Ahmed; Al-Ghamdi, Ahlam A.; Rabindran Jermy, B.; Abouelhoda, Mohamed; Subhani, Shazia; Al Asoom, Lubna; Borgio, J. Francis (Frontiers in Medicine, 2021)
Family trio next-generation sequencing-based variant analysis was done to identify the genomic reason on unexplained recurrent pregnancy loss (RPL). A family (dead fetus and parents) from Saudi Arabia with an earlier history of three unexplained RPLs at the ninth week of pregnancy was included in the study. Whole-genome sequencing (WGS) of a dead fetus and the parents was done to identify the pathogenic variation and confirmed through Sanger sequencing. WGS of dead fetus identifies a novel homozygous exonic variation (NM_017419.3:c.680G>T) in ASIC5 (acid-sensing ion channel subunit family member 5) gene; the parents are heterozygous. Newly designed ARMS PCR followed by direct sequencing confirms the presence of heterozygous in one subject and absence of homozygous novel mutation among randomly selected healthy Saudis. The second family with heterozygous was confirmed with three unexplained RPLs. Pathogenicity analysis of R227I amino acid substitution in ASIC5 protein through molecular docking and interaction analysis revealed that the mutations are highly pathogenic, decrease the stability of the protein, and prevent binding of amiloride, which is an activator to open the acid-sensing ion channel of ASIC5. The identified rare and novel autosomal recessive mutation, c.680G>T:p.R227I (ASIC5Saudi), in two families confirm the ASIC5 gene association with RPL and can be fatal to the fetus.